2012
DOI: 10.2146/ajhp110297
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a pharmacist-led, multidisciplinary diabetes management team

Abstract: Implementation of a pharmacist-led, multidisciplinary DMT helped to achieve intensive glycemic control in CABG patients and decrease the rate of infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 9 publications
0
19
0
Order By: Relevance
“…Several studies supported the favorable effect of pharmacist-led, multidisciplinary team in managing diabetes in different settings [3,14,15]. Mularski et al in a pre-post observational study published in 2012 evaluated the role of a pharmacist-led glycemic control team in managing hyperglycemia in surgical patients with perioperative dysglycemia (diabetes or stress hyperglycemia).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies supported the favorable effect of pharmacist-led, multidisciplinary team in managing diabetes in different settings [3,14,15]. Mularski et al in a pre-post observational study published in 2012 evaluated the role of a pharmacist-led glycemic control team in managing hyperglycemia in surgical patients with perioperative dysglycemia (diabetes or stress hyperglycemia).…”
Section: Discussionmentioning
confidence: 99%
“…In a pre-post, observational study in hospitalized surgical patients with perioperative dysglycemia, the implementation of a glycemic control protocol by a team of trained pharmacists has been associated with a statistically significant improvement in measures of glycemic control as well as with a decrease in the rate of hypoglycemic events in postoperative days [14]. Similarly, in a 3-year prospective survey at a 564-bed medical center in the United States, Warrington et al demonstrated that the development of a pharmacistled, multidisciplinary diabetes management team contributes in achieving glycemic control (serum blood glucose concentrations less than 200 mg/dl) and decrease in the incidence of sternal surgical-site infections in patients undergoing the coronary artery bypass graft (CABG) procedure [15]. According to the American Diabetes Association (ADA) statement, a collaborative team including physicians, nurses, dietitians, pharmacists, and mental health professionals, is necessary to improve medical care of patients with diabetes [2].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research regarding multidisciplinary teamwork has shown that successful interprofessional teamwork helped to achieve intensive glycemic control in certain patient groups 4. However, interprofessional teamwork in general, not solely within diabetes care, has certain difficulties in clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the disease requires the skill and talents of multiple health care providers, and as such, interprofessional teamwork is extremely important for diabetes care 2,3. Successful interprofessional teamwork – in other words, when multiple health workers from different professional backgrounds work together and are able to provide comprehensive services effectively by working with patients, their families, caregivers, and communities – leads to better patient care and safety, and improves health outcomes for patients 47. Therefore, it is not an exaggeration to say that the level of success of interprofessional teamwork may determine diabetes care outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…6 Effective administrative support, adequate human and financial resources, and continual planned assessment of performance by stakeholders, are all factors necessary for the planning, development, implementation, and success of a collaborative care model. 60,61 Although collaboration, in general, has been shown to result in cost savings for the health care system through reduction in frequency of hospitalization and more appropriate medication use, in the majority of studies, however, cost effectiveness of the collaborative care model in improving patient outcomes compared to traditional care was not assessed precisely.…”
Section: Challenges and Barriers In Cppmentioning
confidence: 99%